Analisis Cluster K-Means Kabupaten/Kota di Jawa Timur Berdasarkan Level Epidemik HIV - Desy Yuanita Nugroho; Arief Wibowo (Universitas Airlangga, 2019)
Human Immunodeficiency Virus (HIV) in East Java was not only occurred in urban areas. This is due to the population mobility and sexual lifestyles. This study aimed to classify districts/cities in East Java used Cluster K-Means analysis based on the number of high risk population that living with HIV. This study was an observational study with an analytical method. The secondary data was taken from HIV and PIMS Situation Report of the East Java Provincial Health in 2017. This study obtained 3 optimal clusters, which were 4 districts/cities in cluster 1 named alert category, 24 districts/cities in cluster 2 named standby category and 10 districts/cities in cluster 3 named alert category. Proposed suggestions based on this study were prioritized early HIV test and counseling, provided adequate care, support and treatment for people living with HIV.